Does prostitution constrain sex crimes? Micro-evidence from Korea - Seo-Young Cho (Philipps-University Marburg, School of Business and Economics, 2015)
This paper investigates empirically whether prostitution reduces sex crimes. Theoretical predictions suggest two contradicting effects: substituting or complementing. By using survey data of sex offenders in Korea, I find that prostitution increases the probability of committing sex crimes. Also, the experience of buying sex with a minor exacerbates the severity of sex crimes. These results indicate that prostitution intensifies one's propensities for more violent sexual behaviors, suggesting a complementary relationship between prostitution and sex crimes. The main findings do not alter after accounting for the endogeneity of the model by applying an exogenous instrument - the location of red-light districts.
Keywords: D01; J16; K42; 330; sex crime; prostitution; complementary effects; substitution effects; risky sexual behaviors